Enhancing crop productivity and livelihood security through improved technological interventions in Jabalpur district of Madhya Pradesh - Dubey, R P; Choudhary, V K; R, Chethan C; Singhariya, S; Ghosh, D; Gharde, Y; Singh, P K (Indian Farming, 2022)
.